2023
DOI: 10.1001/jamaneurol.2022.4699
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antiepileptic Drugs and Incident Parkinson Disease

Abstract: ImportanceRecent studies have highlighted an association between epilepsy and Parkinson disease (PD). The role of antiepileptic drugs (AEDs) has not been explored.ObjectiveTo investigate the association between AEDs and incident PD.Design, Setting, and ParticipantsThis nested case-control study started collecting data from the UK Biobank (UKB) in 2006, and data were extracted on June 30, 2021. Individuals with linked primary care prescription data were included. Cases were defined as individuals with a Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Overall, our results confirm the findings of Belete et al [ 5 ], with similar ORs for any AED, sodium valproate, and carbamazepine in both studies. Although Belete et al also found significant positive associations for lamotrigine and levetiracetam, we did not find a significant association for either drug in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, our results confirm the findings of Belete et al [ 5 ], with similar ORs for any AED, sodium valproate, and carbamazepine in both studies. Although Belete et al also found significant positive associations for lamotrigine and levetiracetam, we did not find a significant association for either drug in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Although the association between prescription medications and subsequent diagnosis of PD is of particular clinical relevance, it has not been comprehensively studied. Recently, Belete and colleagues reported that prescriptions of several antiepileptic drugs (AED) are significantly associated with an increased incidence of PD in the UK [ 5 ]. However, the association differed depending on the type of AED, being strongest for valproate (OR: 3.82; 95% CI: 2.41–6.05) and weakest (and statistically non-significant) for carbamazepine (OR: 1.43; 95% CI: 0.97–2.11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found an association between antiepileptics (N03) and increased risk of PD, which was also recently reported in a UK Biobank substudy. 35 The antiepileptic valproic acid is linked to drug-induced tremors, 36 which might lead to either misdiagnosis of PD or an earlier diagnosis of true PD, because of better health monitoring. Moreover, the HR in our time-lagged results decreased quickly toward 1 (no effect) already 5 years before PD diagnosis, arguing for a reverse causal explanation of this association.…”
Section: Discussionmentioning
confidence: 99%
“…In the Original Investigation “Association Between Antiepileptic Drugs and Incident Parkinson Disease in the UK Biobank,” published online December 27, 2022, the title was incorrect and should have appeared as “Association Between Antiepileptic Drugs and Incident Parkinson Disease.” This article has been corrected online.…”
mentioning
confidence: 99%